1994
DOI: 10.3758/bf03202763
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical cross-language priming effects

Abstract: Three experiments were conducted to examine cross-language priming in bilinguals. The first was a cross-language primed lexical decision task experiment with Chinese-English bilinguals. Subjects made lexical decisions about primary associate targets in the two languages at the same rate, but priming occurred only when the prime was in their first language (Ll), Chinese, and the target was in their second language (L2), English. Experiment 2 produced the same pattern of asymmetrical priming with two alphabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
107
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 50 publications
14
107
1
1
Order By: Relevance
“…These and additional studies also showed that translation-equivalent primes facilitated lexical decisions relative to unrelated primes under normal (Altarriba, 1992;Frenck-Mestre & Vaid, 1992;Gollan, Forster, & Frost, 1997;Keatley et al, 1994;Williams, 1994) or deadline (Keatley & de Gelder, 1992) testing procedures. For noncognate translation equivalents, the degree of priming was less than (about 68% of) that observed with identical (same-language) primes (de Groot & Nas, 1991;Frenck-Mestre & Vaid, 1992;Gollan et al, 1997).…”
Section: Immediate Priming Of Lexical Decisionsmentioning
confidence: 93%
See 3 more Smart Citations
“…These and additional studies also showed that translation-equivalent primes facilitated lexical decisions relative to unrelated primes under normal (Altarriba, 1992;Frenck-Mestre & Vaid, 1992;Gollan, Forster, & Frost, 1997;Keatley et al, 1994;Williams, 1994) or deadline (Keatley & de Gelder, 1992) testing procedures. For noncognate translation equivalents, the degree of priming was less than (about 68% of) that observed with identical (same-language) primes (de Groot & Nas, 1991;Frenck-Mestre & Vaid, 1992;Gollan et al, 1997).…”
Section: Immediate Priming Of Lexical Decisionsmentioning
confidence: 93%
“…Between-language facilitation was substantial relative to unprimed targets at an SOA of 500 ms (Frenck & Pynte, 1987). There have also been some discrepant nonsignificant crosslanguage facilitation effects within the same studies at SOAs ranging from 60 ms to 2,000 ms (de Groot & Nas, 1991;Grainger & Beauvillain, 1988 10 ; Keatley et al, 1994) or when a deadline procedure was used (Keatley & de Gelder, 1992).…”
Section: Immediate Priming Of Lexical Decisionsmentioning
confidence: 97%
See 2 more Smart Citations
“…An obvious explanation for this effect is that the concurrent study of several foreign languages can lead to a dilution in attentional resources during the learning process, thus resulting in weaker connections to the semantic representations in each language by adding more noise to the whole system. This is in accordance with multilingual interactive activation models (Grainger & Dijkstra, 1992;Keatley, Spinks & de Gelder, 1994) in that it suggests that the strength of intralingual connections needs to be developed slowly over time. If a student is exposed to both Russian and French vocabulary simultaneously, it will take some time to strengthen the links of each Russian word to the other Russian words and each French word to the other French words, so that these links will come to dominate over any potential links between languages or against background noise.…”
Section: Discussionmentioning
confidence: 50%